Evaluation of Kinetic Parameters of Nitrification Process in Biofilter System to Efluent Liquid Waste of Tofu Industry - Nyimas Yanqoritha; Kuswandi; Sulhatun Sulhatun (Jurnal Penelitian Pendidikan IPA, 2022)
It is necessary to design a nitrification bioreactor process so that further processing takes place optimally. Performance studies are carried out by evaluating the kinetic parameters that apply specifically to the applied process. The Monod model was applied to determine the value of kinetic parameters in designing and operating a bioreactor. This study aims to determine the value of the kinetic parameters to variations in feed concentration (50, 75, and 100%). The mechanism of the reactor process for the decomposition of pollutants, the influent is fed into the reactor with an up-flow pristaltic pump. The decomposition process provides contact time between organic matter and microorganisms, resulting in a good separation from the reactor outlet. The most optimum kinetic parameter value at 100% wastewater concentration with a value of (k) 1.1086 (dayË‰ 1), (Ks) 1.0564 g l-1, (Y) 5.4862 mg MLVSS/mg, (kd) 1.7944 (dayË‰ 1), (Âµm) 6.8372 (dayË‰ 1).